Project Management Professional (PMP) examination specification (Project Management Institute, 2005)
In 2004 the Project Management Institute (PMI®) conducted a new global role delineation study to update the Project Management Professional (PMP®) credentialing examination. The study results are used to establish the Project Management Professional (PMP) Examination Specification for the examination, describing the tasks (competencies) that PMPs perform and the project management knowledge and skill PMPs use to complete each task.